2000
DOI: 10.1007/s003309900294
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in ureteral complications of renal transplantation: value of static fluid MR urography

Abstract: Ureteral obstruction is an infrequent complication after renal transplantation that may cause rapid loss of transplant function. We tested static fluid MR urography for determining the cause of graft hydronephrosis. Magnetic resonance urography was performed in nine transplants with dilated collecting systems on ultrasound. A heavily T2-weighted 3D turbo spin-echo sequence on a 1.5-T scanner was used and maximum intensity projections were obtained. The patients also underwent excretory urography (n = 1), renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 27 publications
(46 reference statements)
1
5
0
Order By: Relevance
“…The sensitivity, specificity and overall accuracy for Gdenhanced MRU in detection of ureteral obstruction were 80%, 100% and 98.9% and for both heavy T 2 W and single-shot MRU they were 100%. These results concerning static heavy T 2 W MRU were comparable to those reported by Schubert et al (13) and were 80%, 100% and 98.8%.…”
Section: Discussionsupporting
confidence: 80%
“…The sensitivity, specificity and overall accuracy for Gdenhanced MRU in detection of ureteral obstruction were 80%, 100% and 98.9% and for both heavy T 2 W and single-shot MRU they were 100%. These results concerning static heavy T 2 W MRU were comparable to those reported by Schubert et al (13) and were 80%, 100% and 98.8%.…”
Section: Discussionsupporting
confidence: 80%
“…"All-in-one approach" MR procedures, such as conventional sequences, MR angiography and MRU, are advocated for evaluation of renal transplants [28,29,30]. Insignificant nephrotoxicity of gadolinium chelates allows performance not only of sMRU but also excretory MRU in the patients after renal transplantation, even in those with increased level of creatinine (although it is suggested that the level of serum creatinine would not exceed 4 mg/dl).…”
Section: Discussionmentioning
confidence: 99%
“…When examining renal transplants with MR urography, it is advantageous to combine static-fluid with excretory phase sequences, provided sufficient renal function is present. Schubert et al (65) studied nine renal transplant recipients with static-fluid MR urography and found the lack of functional information to be limiting. In their small series, static-fluid MR urography revealed a definite cause of obstruction in only two of five cases (65).…”
Section: Pre-and Postoperative Assessmentmentioning
confidence: 98%
“…Schubert et al (65) studied nine renal transplant recipients with static-fluid MR urography and found the lack of functional information to be limiting. In their small series, static-fluid MR urography revealed a definite cause of obstruction in only two of five cases (65). Static-fluid MR urography may not be capable of helping to distinguish between ureteral obstruction and vesicoureteral reflux in some cases, and ureteral leak cannot be demonstrated in the absence of excreted contrast material.…”
Section: Pre-and Postoperative Assessmentmentioning
confidence: 98%